Pemberitaan Media Informasi Sebagai Bahan Rujukan Pengambilan Keputusan Transaksi Saham Di Valbury Asia Securities Cabang Dago Bandung - Iin Rahmi Handayani (KOM & REALITAS SOSIAL, 2011)
This research aims to reveal the use of information media as reference for investor Valbury Asia Securities Dago branch Bandung to making decision in stock market transaction. And how all the event sequences across the world is connected as a whole complete system based on Littlejohn System Theory. This research design was qualitative with descriptive method. Technique that used to collect the data are using depth interview, observations and document literature. The numbers of informants are 2 base informants and 6 key informants. This research result show the activity of information media usage as a reference to make decision in stock transaction is determined by a kind of stock investment and motivation of each investor.Â Investor using logic decision in transaction will more actively use information media than investor using instinct and trend as decision in transaction. Variety of events all around the world are connected each other in influencing a condition of stock market as a complete system entity matched to Littlejohn System Theory.